School violence and its psychological impacts: A comparative analysis in the context of Vietnam. - Le, Thuy Thi Thanh; Le, Hien Thu; Dao, Tinh Thi; Nguyen, Muoi Thi; Nguyen, Nga Thi Thanh (International Journal of Innovative Research and Scientific Studies, 2025)
Globally, school violence affects kids' academic performance, mental health, and social development. International research uses varied methods to study school violence, but Vietnamese studies are mostly quantitative and lack methodological rigor and psychological analysis. Synthesizing global and Vietnamese school violence literature to identify trends, research constraints, and intervention techniques attempts to fill these gaps. This systematic literature analysis investigated empirical studies from Google Scholar, UNESCO, UNICEF, and WHO databases from 2000 to 2024. Relevant studies were chosen for school violence prevalence, causes, psychological effects, and interventions. A thematic analysis categorized findings by methodological approach and study emphasis, followed by a comparative analysis of international and Vietnamese studies. Physical, psychological, social, and cyber school violence exists, with psychological violence being more common. International studies use standardized instruments and mixed-method approaches, while Vietnamese research uses self-constructed assessment tools with inadequate validation. Family environment, peer dynamics, school atmosphere, and media influence are important. Life skills education and punishment dominate Vietnamese intervention efforts, while international programs emphasize social-emotional learning, teacher training, and community involvement. Qualitative research in Vietnam needs better methods and established measurement tools. Effective prevention should move from punitive to evidence-based, multi-stakeholder interventions. Future school violence intervention program evaluations should use mixed-method approaches and longitudinal assessments. This review helps Vietnamese policymakers and educators create more comprehensive school violence prevention strategies.